Penggunaan Teknik Mind Mapping Pembelajaran Bahasa Indonesia Untuk Meningkatkan Pemahaman Konsep Siswa : The Use of Mind Mapping Technique in Indonesian Language Learning to Improve Students' Conceptual Understanding - Pratiwi, Brillianing; Abas, Kusnadiyanto (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to evaluate the effectiveness of using Mind Mapping techniques in improving students' conceptual understanding in Indonesian language lessons, especially in the material on understanding the concept of a reading, in class VI C SDN 3 Palu, Palu City. This study uses a Classroom Action Research (CAR) approach that involves the process of planning, implementing, observing, and reflecting in three cycles: pre-cycle, cycle 1, and cycle 2. The results of the study showed a significant increase in students' understanding and performance from cycle to cycle. The application of Mind Mapping techniques successfully increased the average student score from 57 in the pre-cycle to 82.5 in cycle 2, with the percentage of completion increasing from 40% to 90%. However, this study identified several obstacles in the application of the Mind Mapping method, including differences in students' cognitive abilities, difficulties in connecting sub-concepts, and the need for materials such as paper and cardboard. Solutions to overcome these obstacles include providing special guidance to underprivileged students, taking notes and creating complex keywords, and ensuring the availability of the necessary materials. This study provides insight for teachers in choosing effective learning methods and provides recommendations for developing better learning strategies in the future.